Chemical modification of implantable biologic tissue for anti- calcification - Park, Ki Dong; Yun, Ju Young; Han, Dong Keun; Jeong, Seo Young; Kim, Young Ha; Choi, Kyu Suk; Kim, Hyoung Mook; Kim, Hack Joo; Kim, Kwang Taek (J.B. Lippincott Co, Hagerstown, 1994)
Biologic porcine tissue was modified by coupling sulfonated polyethyl- eneoxide (PEO-SO3) and the effect of modification on calcification was evaluated in vitro and in vivo. The modification process involves grafting PEO-SO3 to porcine valve leaflet either by carbodiimide (EDC) activation or by direct coupling using glutaraldehyde. Thermal property, measured by differential scanning calorimetry, showed that the shrinkage temperature of modified tissue increased compared with control tissue and fresh tissue, suggesting increased thermal stability. Resistance to collagenase digestion revealed that modified tissues have greater resistance to enzyme digestion than do control tissues. In vitro calcification showed that modified tissues have less calcium deposition than do control tissues. In vivo calcification, using a rat subcutaneous implantation model, also showed less calcification of modified tissue than that of control. The resistance of modified tissue to collagenase, higher shrinkage temperature, and reduced calcification, when compared with control tissue, attest to the usefulness of this chemical modification for implantable biologic tissue.Biologic porcine tissue was modified by coupling sulfonated polyethyl-eneoxide (PEO-SO3) and the effect of modification on calcification was evaluated in vitro and in vivo. The modification process involves grafting PEO-SO3 to porcine valve leaflet either by carbodiimide(EDC) activation or by direct coupling using glutaraldehyde. Thermal property, measured by differential scanning calorimetry, showed that the shrinkage temperature of modified tissue increased compared with control tissue and fresh tissue, suggesting increased thermal stability. Resistance to collagenase digestion revealed that modified tissues have greater resistance to enzyme digestion than do control tissues. In vitro calcification showed that modified tissues have less calcium deposition than do control tissues. In vivo calcification, using a rat subcutaneous implantation model, also showed less calcification of modified tissue than that of control. The resistance of modified tissue to collagenase, higher shrinkage temperature, and reduced calcification, when compared with control tissue, attest to the usefulness of this chemical modification for implantable biologic tissue.
Keywords: Calcification (biochemistry); Calorimetry; Chemical modification; Composition effects; Grafting (chemical); Physiological models; Thermal effects; Thermodynamic stability; Tissue; Biologic porcine tissue; Carbodiimide activation; Collagenase digestion; Coupling sulfonated polyethyl-eneoxide; Differential scanning calorimetry; Enzyme digestion; Glutaraldehyde; Implantable biologic tissue; Shrinkage temperature; Implants (surgical); collagenase; cyanamide; macrogol derivative; animal experiment; animal tissue; article; calcification; chemical modification; differential scanning calorimetry; enzyme activity; implantation; nonhuman; postoperative complication; rat; swine; thermostability